Transfigurasi Hukum Islam dalam Sistem Hukum Nasional - Yusdani - (Unisia, 2003)
Transfiguration of islamic law into Indonesian legal system is seen as a way to the legalization of fiqh into modem legal system. To make this transfiguration run smoothly, the process should be built on the full recognition of political and scientific dynamics in society. Thus, far from the classical theory of receptie during early colonialization era, this transfiguration must be made in the corridor of democracy and academic maturity.